Comparison of the umbilical cord Blood’s anti-Mullerian hormone level in the newborns of mothers with polycystic ovary syndrome (PCOS) and healthy mothers - Tadaion Far, Faezeh (J Ovarian Res, 2019)
BACKGROUND: Polycystic ovary syndrome (PCOS) is one of the most common endocrine diseases. At present, the cause of the disease is not fully understood, but many studies have shown that PCOS is associated with genetic and environmental factors. The present study aimed to assess the umbilical cord blood’s Anti-mullerian hormone (AMH) level in the newborns of mothers suffering from PCOS comparing to healthy mothers. METHODS: This prospective cohort study was conducted on 120 pregnant women with PCOS, who were selected through Rotterdam criteria, and 60 healthy pregnant women as the control group. The subjects in each group were divided into obese and non-obese mothers according to their body mass index (BMI) before pregnancy. The cord blood samples were collected from the offsprings on the time of childbirth. Finally, the circulating concentrations of AMH in both sexes of the newborns were determined by specific assays. RESULTS: The research results showed that the blood level of AMH was higher in the neonates of obese mothers with PCOS comparing to the controls (P < 0.001). Mean AMH level was higher in male neonates born from non-obese PCOS mothers than in the controls (P < 0.001); however, there was not a significant difference in the level of AMH in female neonates between these two groups (P = 0.264). Also the level of the above biomarker was higher in both sexes of the neonates belonging to obese PCOS mothers compared with the neonates born from non-obese PCOS mothers (P < 0.001). CONCLUSION(S): It can be said that the cord blood AMH level of neonates from obese women with PCOS is higher than that in the newborns of non-obese PCOS mothers. Further longitudinal studies are needed to confirm the clinical findings of the present research.